Plenty of room on the top: pathways and spectroscopic signatures of singlet fission from upper singlet states - Bai, Yiting (2023)
We investigate dynamic signatures of the singlet fission (SF) process triggered by the excitation of a molecular system to an upper singlet state SN (N > 1) and develop a computational methodology for the simulation of nonlinear spectroscopic signals revealing the SN → TT1 SF in real time. We demonstrate that SF can proceed directly from the upper state SN, bypassing the lowest excited state, S1. We determine the main SN → TT1 reaction pathways and show by computer simulation and spectroscopic measurements that the SN-initiated SF can be faster and more efficient than the traditionally studied S1 → TT1 SF. We claim that the SN → TT1 SF offers novel promising opportunities for engineering SF systems and enhancing SF yields.